Hubungan Sikap Dengan Motivasi Dalam Memberikan Pertolongan Pertama Dalam Kasus Kecelakaan Pada Siswa SMAN 2 Limboto Kabupaten Gorontalo - Pipin Yunus; Haslinda Damansyah; Ani Retni; Arief Y Salam (NAJ : Nursing Applied Journal, 2023)
An accident is an unplanned and unwanted event by any person that can cause injury, illness, or material damage. This study aims to determine the relationship between attitude and motivation in providing first aid in the case of an accident to students of SMA Negri 2 Limboto, Gorontalo Regency. This research uses a type of quantitative correlation research with a cross sectional method. Sampling in this study was carried out using a probability sampling technique, namely proportionate stratified random sampling with a total sample of 87 respondents. Data collection using observation sheets and questionnaires. data analysis using the Chi Square statistical test was obtained p = 0.000 with <0.05, then Ha was accepted, so it can be concluded that there is a relationship between attitude and motivation in providing first aid in the case of accidents in students of Sman 2 Limboto, Gorontalo Regency